Bisphosphonate-Based Strategies for Bone Tissue Engineering and Orthopedic Implants - Cattalini, Juan Pablo (2012)
Bisphosphonates (BPs) are a group of well-established drugs applied in the development of metabolic bone disorder-related therapies. There is increasing interest also in the application of BPs in the context of bone tissue engineering which is the topic of this review in which an extensive overview of published studies on the development and applications of BPs based strategies for bone regeneration is provided with special focus on the rationale for the use of different BPs in three dimensional (3D) bone tissue scaffolds. Different alternatives investigated to address the delivery and sustained release of these therapeutic drugs in the nearby tissues are discussed comprehensively and the most significant published approaches on bisphosphonate-conjugated drugs in multifunctional 3D scaffolds as well as the role of bisphosphonates within coatings for improved fixation of orthopaedic implants are presented and critically evaluated. Finally, the authors’ views regarding the remaining challenges in the fields and directions for future research efforts are highlighted.